The Effect of Competencies and Independence Internal Auditors on Internal Audit Quality: The Theoretical Review Approach - Ahmadi Aidi; Sayuthi Sayuthi; Imam Susanto; Ahmad Junaidi; Abdurohim Abdurohim (Ilomata International Journal of Tax and Accounting, 2022)
This research was conducted at the Indonesian Financial and Development Supervisory Agency (BPKP) at Jalan Pemuda No 33 Jakarta. The time of the study starts in January 2018 until September 2018. This study aims to determine the influence of the competence and independence of the auditor internal on the quality of internal audit and its impact on the effectiveness of internal control. The study sample consisted of 63 people from auditors at the Indonesian BPKP. Primary data is obtained through observation, interviews, and questionnaires whose validity and reliability have been tested first. The object in this study is the influence of competence and independence of internal auditors, as well as the quality of internal audit, while those who are the subject of this research are BPKP RI auditors. The conclusions obtained are there is a significant influence of the competence and independence of internal auditors on the quality of internal audit together.